Sustainable fishery: Combating IUU fishing through people's participation to ensure environmental justice. (3rd July 2022) - Kumar, Anand; Parameswaran, K.
ABSTRACT: The world ocean is a continuum that facilitates relatively free interchange among its parts and is of fundamental importance to studying environmental justice. Environmental justice sits within the larger ambit of social justice and equity. The article examines the effects of illegal, unreported, and unregulated (IUU) fishing within the Indian Ocean Region (IOR) on sustainability, and damage to the marine ecology, resulting in environmental and distributive injustice to the coastal communities. It also highlights the prevalence of IUU fishing on the high seas and in the exclusive economic zones (EEZ) of the coastal States vis-à-vis existing international fisheries laws. In addition, the article analyses the feasibility of managing the marine environment in the IOR through people's participation, utilising the tenets of Commander's Estimate of the Situation (CES), and suggests courses of action (CoAs) to achieve environmental justice. Further, it makes use of three case studies to assess the feasibility of people's participation in achieving sustainable fishing practices.